Identification of Nonlinear Dynamic Behavior and Failure for Riveted Joint Assemblies. (2000) - Langrand, B.; Markiewicz, E.; Deletombe, E.; Drazétic, P.
Abstract : Many different types of rivets need to be modeled to analyze the crashworthiness of aircraft structures. A numerical procedure based on FE modeling and characterization of material failure constitutive models is proposed herein with the aim of limiting the costs of experimental procedures otherwise necessary to obtain these data. Quasi-static and dynamic experiments were carried out on elementary tension (punched) and shear (riveted) specimens. No strain rate sensitivity was detected in the failure behavior of the riveted joint assemblies. Experimental data were used to identify the Gurson damage parameters of each material (2024-T351 and 7050 aluminum alloys for the sheet metal plate and the rivet respectively) by an inverse method. Characterization gave rise to satisfactory correlation between FE models and experiments. Optimized parameters were validated for each material by means of a uniaxial tension test for the sheet metal plate and an ARCAN type specimen in pure tension for the rivet.